Sex education in eighteenth-century France - Agin, S (Voltaire Foundation, 2017)
Did ‘sex education’ actually exist in eighteenth-century France? Shaped by competing currents of religious dogma, atheist materialism and bourgeois morality, eighteenth-century France marked the beginning of what Michel Foucault called ‘une fermentation discursive’ on matters related to sex. But when we consult the educational theorists or philosophes of the time for their opinions on preparing a young person for life as a sexual being, we are met with a telling silence. Did an Enlightenment era that dared to make sex an object of discourse also dare to make it an object of pedagogy? Sex education in eighteenth-century France brings together specialists from a range of disciplines to address these issues. Using a wide variety of literary, historical, religious and pedagogical sources, contributors explore for the first time the nexus between sex and instruction. Although these two categories were publicly kept distinct, writers were effectively shaping attitudes and behaviours. Unraveling the complex system of rules and codes through which knowledge about sex was communicated, contributors uncover a new dimension in the practice of education in the eighteenth century. Shane Agin, Introduction: sex education in eighteenth-century France I. Regulation Jean Bloch, Perdition, degeneration or legitimate pleasure? Eighteenth-century French education and the subject of sex Allan H. Pasco, Miss Manners and fooling around: conduct manuals and sexual mores in eighteenth-century France Paul Scott, Rites of wrong: confessors’ manuals and sins of the flesh in eighteenth-century France Kathryn A. Hoffmann, Curing masturbation with a bath, a straitjacket or a wax museum: the strategies of Tissot, Bienville and Bertrand-Rival II. Reflection and evaluation Jean M. Goulemot, Sex education in early modern utopian literature: an investigation into the margins Matthew Lauzon, Dangerous educations and factitious puberties: the enlightening lessons of foreign love Shane Agin, The construction and education of the sexualised subject in Rousseau Cecilia Feilla, Correspondence school for lovers: epistolary exchange and sexual education in Restif de la Bretonne’s Le Nouvel Abeilard III. Narratives of education, initiation and discovery Didier Masseau, Representations of sexual awakening in eighteenth-century memoirs Chris Roulston, Female education and sex education in Choderlos de Laclos’s Les Liaisons dangereuses Jean-Christophe Abramovici, The comedy of ignorance: scenes of sexual initiation in early modern pornographic literature Juliette Cherbuliez, The science of seduction: libertinism’s privileged spheres of knowing James Grantham Turner, Sexual awakening as radical Enlightenment: arousal and ontogeny in Buffon and La Mettrie Summaries Bibliography Index